Bundling climate smart agriculture and climate information services: the CSA Bundler Application - Tepa Yotto, Ghislain; Dalaa, Mustapha Alasan; Obeng Adomaa, Faustina (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Climate smart agriculture (CSA) implementation can be challenging in instances where promoting single standalone CSA practices or technologies would hardly achieve the expected triple-win climate smartness outcome with maladaptation and stagnation risks in a business as usual scheme. To the best of our knowledge and based on consulted literature, there is little data about climate smart agriculture (CSA) and climate information services (CIS) bundling. The current brief aims at documenting an approach developed under the framework of the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project for CSA and CIS bundling through stakeholder consultations in Ghana. Erratic rainfall, prolonged drought and dry spells, decline in yields, and pest outbreaks were scored top five (5) primary climate challenges by stakeholders. Other challenges of importance included soil fertility, irrigation and water management, and access to inputs and finance. Five priority value chains were selected including maize, rice, cowpea, yam, and vegetables. To achieve inclusiveness, soybean, groundnut, cocoa, poultry and goat were added as strategic value chains with high value addition potential. Climate smart agriculture (CSA) and climate information services (CIS) bundles around these value chains were prioritized for scaling in ten regions in Ghana: Bono, Bono East, Central, North East, Northern, Oti, Savannah, Upper East, Upper West and Volta. Insights from stakeholder perspectives indicated preference for the following CSA practice and technology types as key to building climate resilience: high-yielding varieties, early-maturing varieties, drought-tolerant varieties, integrated soil fertility management including the use of organic fertilizers, irrigation and water management, integrated pest and disease management, improved breeds, improved postharvest techniques, and climate information services and advisories. Gender and social inclusiveness (GSI) was explored to map relevant CSA practices and technologies for male, female, youth (male and female), and commercial farmers. Generic customizable bundles of CSA-CIS were explored using basic ecosystem and climate risk metrics. A stepwise CSA-CIS investment bundling was designed considering a full CSA investment principle that consists of triple-win productivity-adaptation-mitigation benefits of CSA. The current brief describes a basic CSA-CIS bundling approach using simple metrics. It provides new insights for developing an appealing tool called “CSA Bundler”. The CSA Bundler has potential for further advancement into web- or phone-based applications and with robust algorithms or AI component integration for accurate and high-resolution site-specific recommendation